Bibliometric Analysis of Artificial Intelligence in Utilized Distance Education and Distance Learning Studies - Ay, Sevinc; Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2024)
In the contemporary era, wherein artificial intelligence is gaining increasing prominence, its presence and significance are being witnessed in various facets of our daily lives. It is widely believed that artificial intelligence will pave the way for novel advancements in the realm of education, a domain that is profoundly influenced by its influence. Consequently, delving into the ramifications of artificial intelligence on distance education, which has become an integral component of the educational process, assumes paramount importance. This study undertook a comprehensive bibliographic analysis, utilizing data sourced from the Web of Science database encompassing the period between 1993 and 2024, obtained through searches employing the keywords 'artificial intelligence' and 'distance learning' or 'distance education'. The findings were assessed based on keywords, authors, documents, sources, and countries. While the keywords were thoughtfully diversified to ensure that studies in this domain were not inadvertently overlooked, the outcomes reveal that there exists ample scope for further research in this field, necessitating the publication of new scientific works. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: artificial intelligence; bibliometric analysis; distance education; distance learning